THE IMPACT OF ADMINISTRATIVE DECENTRALIZATION ON LOCAL GOVERNMENT PERFORMANCE - Diyan Ramadhani; Aan Adiazmil (Public Studies and Business Administration Journal (PUSBA), 2025)
Administrative decentralization has become an important strategy in government reform in various countries, with the aim of improving regional government performance through increasing efficiency, effectiveness and accountability. This research conducts a systematic review of existing literature to explore the impact of administrative decentralization on local government performance, as well as identifying factors that influence the success or failure of its implementation. The results of the analysis show that the impact of decentralization is varied, depending on the institutional context, administrative capacity and national policy support. Although decentralization can improve public services, challenges such as resource inequality and corruption at the local level often hinder their effectiveness. This research provides policy recommendations to increase the effectiveness of decentralization, including strengthening administrative capacity, proportional fiscal decentralization, and improving accountability mechanisms. It is hoped that these findings can become a reference for policy makers and academics in designing more effective decentralization policies.